THE CORRELATION BETWEEN STUDENTS’ COGNITIVE AND AFFECTIVE ASPECT WITH THEIR SPEAKING PERFORMANCE - Muh. Nurasyik; Ummi Khaerati Syam; Sitti Maryam Hamid (Indonesian Journal of Psycholinguistics, 2022)
This research aimed to know the the correlation between students’ cognitive and affective aspect with their speaking performance at the eleventh grade students of SMAN 11 Gowa. The subjects of this research consisted of 33 students at the eleventh grade MIA of SMAN 11 Gowa. The research design that was used was a kind of the correlation research. The instruments used for collecting data namely intelligence test and questionnaire. The result of the data indicated that, the students’ mean score of cognitive aspect especially intelligence test was 67.57. While mean score of affective aspect especially questionnaire was 50.78. Moreover, based on the data analysis, the pearson correlation was 0.479, that was classified as an enough correlation where standard correlation lies between 0.400 – 0.599. Then the T-Test value is 3,039, while the T table is 1,669. Therefore, it can be said that Ha is accepted and Ho is rejected. The value is 5. 145>1. 694 and the value of Sig. Lower than 0.05, which can be said to have a significant positive effect between cognitive and affective aspect. It meant that the cognitive aspect of the students influenced the students’ affective aspect in speaking performance. Thus, the students need to have a good knowledge and self-confidence because it correlated to make their speaking performance good.